Diagnóstico organoléptico, inorgánico y microbiológico del agua potable consumida por la población del distrito de Trujillo - Quispe Quiroz, María Del Carmen (2008)
This work presents a "DIAGNOSIS ORGANOLIPTICO, INORGANIC AND MICROBIOLOGICAL OF THE DRINKABLE WATER CONSUMED BY THE POPULATION OF THE DISTRICT OF TRUJILLO ", it has as principal aim, the determination and evaluation of the quality parameters of the drinkable water consumed by the above mentioned District. There is wished that by means of this work that one is aware to the water access of good quality for the settler. The quality water inside the ideal parameters must treat as a social good, of health and culturally, and not principally as an economic good; to assure progressively that the whole world should have access to drinkable sure water and sanitary facilities equitably, without discrimination. Since it is a determinant factor of the bill of health of a population. According to the WORLD ORGANIZATION OF THE HEALTH, the drinkable water must be clean, fresh, without flavors or disagreeable smells or that cause rejection of those who consume them, and without chemical substances and harmful microorganisms. Of the studies realized in this work, between the principal aims I come to him to the following conclusions: According to the microbiological realized analysis, it was obtained like proved he does not attend it of Coliformes Totales, in agreement to the Bacteriological Parameters given by DIGESA (1). According to the physicochemical analysis it comes near to the conclusion of which 80 % of the evaluated waters are suitable, and the rest they perform harmful to the health of the settler